John Coates : the man who built The Snowman : a biography of the producer of The snowman, Yellow submarine and many other films-- - Beardmore, Marie (John Libbey, 2012)
"John Coates is best known as the producer of The Snowman, When the Wind Blows, Wind in the Willows, Willows in Winter, and Famous Fred, and as the man behind the Beatles film Yellow Submarine. This intimate biography takes the reader on a journey through Coates's early life, his years as an army officer in the 11th Hussars in World War II, and his postwar life as a distributor for Rank films throughout Asia, before returning to England and eventually taking over TV Cartoons. With a foreword by Raymond Briggs and an epilogue by Coates himself, this abundantly illustrated work also includes a DVD of selections from Coates's work."--Distributor's website